A Distant Reading Electronic Anemo- meter and a Selsyn Operated Windvane (MAUSAM, 1950)
With the increase in aviation, the requisitions for meteorological reports from aerodromes have also increased appreciably. The data have to be supplied both for the planes in the air and in the ground with the least possible delay. Different types of Instruments have been constructed to measure the velocity and direction of surface wind from the room of the observer without going up to the anemometer or windvane which are usually located In places not easily accessible. The present paper describes an equipment consisting of an electronic wind speed indicator and a wind vane using selsyn motors. In the electronic wind speed indicator, an r. f. voltage with a frequency of :0 Kcs. generated in the observer's room is fed through a pair of cables into a coil fixed in the box carrying the spindle of the 4-cap anemometer. Another coil is fixed just below the first coil and the voltage induced in this is fed into an amplifier through a pair of shielded cables. A brass circular vane with ten sector fixed on the anemometer spindle and rotating in the space between the two coils makes the induced voltage fluctuate at a frequency which is proportional to the rate of rotation of the anemometer cups. The induced voltage is amplified and the varying portion of the voltage further amplified and converted into square wave pulses of constant amplitude and then fed into a frequency discrimination circuit which indicates the frequency of the voltage variation by means of a micro-ammeter calibrated in miles per hour. The paper also describes the advantages of this method over some of the other methods in use.